Screening Scale for Behavioral and Socioeconomic Risk Factors for Gambling Addiction: A Validity and Reliability Study - Tekin, Kinyas; Guliyev, Cavid; Yilmaz, Emre; Ogel, Kultegin; Yuksel, Begum Ceren (Turkish Green Crescent Soc, 2020)
This study aimed to develop a measurement tool suitable for determining the gambling risk levels in Turkey. A total of 128 outpatients at two facilities with complaints of gambling were included in the study. The South Oaks Gambling Screen (SOGS) was used in the study. The Gambling Risk Screening Scale (GRSS), which evaluated the level of gambling risk, was developed. The GRSS has two factors-gambling behavior and economic and social problems-and they account for 59% of the total variance. The factor loadings for the first factor ranged from 0.55 to 0.77, whereas for the second factor, the factor loading ranged from 0.77 to 0.95. The Cronbach's alpha of the entire scale was 0.84 and that of its subscales were 0.82 and 0.89. The cutoff point of the scale was 9.5, its sensitivity was 0.98, and its specificity was 0.87. The GRSS scores correlated statistically with the SOGS scores. These findings indicated that GRSS could be considered a valid and reliable scale for determining the gambling risk levels.
Keywords: Gambling; Addiction; Scale; Behavioral Addiction; Validity And Reliability; Protective Factors; Impulsivity; Disorder; Family